Development of a silicon based polarimeter for the low energy prototype proton EDM ring. (1st September 2022) - Gooding, J.; Bowcock, T.; Casse, G.; Price, J.; Rompotis, N.; Vilella, E.; Vossebeld, J.
Abstract: This article details the design of a silicon based polarimeter for use in a prototype storage ring for proton EDM (Electric Dipole Moment) studies. The polarimeter consists of layers of LGAD (Low Gain Avalanche Diode) sensors for a low material budget, time-of-flight measurement and complemented with HV-CMOS (High Voltage CMOS) sensors for accurate scattering angle measurement and tracking. This design has the objective to optimize the polarization measurement of protons with energy 30–45 MeV. Simulations show that the excellent time resolution of LGAD sensors provides a sufficient energy resolution to meet the experiment specifications. HV-CMOS sensors are included to provide complementary spatial resolution with minimal additional material budget. The simulations show that the detector configuration is capable of measuring the scattering angle of a proton scattered off a carbon target to just a few hundredths of a degree. The time-of-flight measurement performance is demonstrated with lab experiments using electrons from a Sr90 source.